Expression profiling of FSHD-1 and FSHD-2 cells during myogenic differentiation evidences common and distinctive gene dysregulation patterns. - Stefania Cheli; Stephanie François; Beatrice Bodega; Francesco Ferrari; Elena Tenedini; Enrica Roncaglia; Sergio Ferrari; Enrico Ginelli; Raffaella Meneveri (PLoS ONE)
Background Determine global gene dysregulation affecting 4q-linked (FSHD-1) and non 4q-linked (FSHD-2) cells during early stages of myogenic differentiation. This approach has been never applied to FSHD pathogenesis. Methodology/principal findings By in vitro differentiation of FSHD-1 and FSHD-2 myoblasts and gene chip analysis we derived that gene expression profile is altered only in FSHD-1 myoblasts and FSHD-2 myotubes. The changes seen in FSHD-1 regarded a general defect in cell cycle progression, probably due to the upregulation of myogenic markers PAX3 and MYOD1, and a deficit of factors (SUV39H1 and HMGB2) involved in D4Z4 chromatin conformation. On the other hand, FSHD-2 mytubes were characterized by a general defect in RNA metabolism, protein synthesis and degradation and, to a lesser extent, in cell cycle. Common dysregulations regarded genes involved in response to oxidative stress and in sterol biosynthetic process. Interestingly, our results also suggest that miRNAs might be implied in both FSHD-1 and FSHD-2 gene dysregulation. Finally, in both cell differentiation systems, we did not observe a gradient of altered gene expression throughout the 4q35 chromosome. Conclusions/significance FSHD-1 and FSHD-2 cells showed, in different steps of myogenic differentiation, a global deregulation of gene expression rather than an alteration of expression of 4q35 specific genes. In general, FSHD-1 and FSHD-2 global gene deregulation interested common and distinctive biological processes. In this regard, defects of cell cycle progression (FSHD-1 and to a lesser extent FSHD-2), protein synthesis and degradation (FSHD-2), response to oxidative stress (FSHD-1 and FSHD-2), and cholesterol homeostasis (FSHD-1 and FSHD-2) may in general impair a correct myogenesis. Taken together our results recapitulate previously reported defects of FSHD-1, and add new insights into the gene deregulation characterizing both FSHD-1 and FSHD-2, in which miRNAs may play a role.